PEREMPUAN DAN KORUPSI PADA RANAH PUBLIK (Ditinjau dari Gaya Kepemimpinan, Politik, Agama, Psikologi dan Budaya Ketimuran) - DEWI SEKAR KENCONO, DEWI SEKAR KENCONO (Program Magister Ilmu Politik, Universitas Diponegoro, 2012)
ABSTRAKSI Corruption is a transnational crime that involves many parties together in the eradication and prevention efforts. The emergence of several names of women involved in cases of corruption in the public good of members of political parties and public officials in the spotlight for several years. Women who are entangled in corruption cases occurred basically due to not knowing the details of the risk positions and the pressure to be received from the position of being diembanya. Judging from the style factor of leadership, political, religious, psychological and oriental cultures all indirectly become patron of women from the bondage of corruption. This is due to the limitations that can not be passed by women both normative and outwardly. Keyword: women, corruption, public